سبل استثمار المقاربة التواصلية في تعليم الدرس البلاغي وتعلمه في السنة الرابعة من التعليم المتوسط " الكناية، الاستعارة، الأسلوب الانشائي أنموذجا" - مصباحي, زينب; حمدان, سليم (University of Eloued جامعة الوادي, 2024)
سعيا لتحسين جودة التعليم، و إكساب المتعلم الكفاية التواصلية اهتم أهل الاختصاص بإدراج ما يسمى تدريس اللغة التواصلي ، ويعد من ابرز ما ارتكزت عنه المناهج الحديثة في الممارسات التعليمية، بغية تنمية قدرات المتعلم واقحامه كجزء لا يتجزأ من مثلث العملية التعليمية ، وفي مقالنا هذا تناولنا المقاربة التواصلية، بشكل موجز ، وسبل استثمارها في تعليم الدرس البلاغي ، وقد حاولنا استقصاء مفهومها ، وخلفيتها، وعلاقتها بالتداولية هذه الأخيرة التي ساهمت بشكل كبير في تطوير العملية التعلمية ، أضف الى ذلك واقع توظيف المقاربة التواصلية في تدريس البلاغة . Abstract: In an effort to improve the quality of education and provide the learner with communicative competence, specialists have taken an interest in including what is called communicative language teaching, and it is considered one of the most prominent aspects on which modern curricula are based in educational practices, in order to develop the learner’s abilities and include him as an integral part of the triangle of the educational process. In this article, we discussed the approach. Communicative, briefly, and ways to invest it in teaching the rhetorical lesson. We have tried to investigate its concept, its background, and its relationship to pragmatics, the latter of which has contributed greatly to developing the learning process, in addition to the reality of employing the communicative approach in teaching rhetoric
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي
Keywords: المقاربة الوظيفية; اللسانيات التداولية; تعليمية اللغة العربية; آليات المقاربة الوظيفية; البلاغة; functional approach; pragmatic linguistics; Educational Arabic language; Mechanisms of the functional approach; rhetoric